The effect of a plasma next-generation sequencing test on antimicrobial management in immunocompetent and immunocompromised patients-A single-center retrospective study - Denise Marie A. Francisco; Laila Woc-Colburn; Travis J. Carlson; Todd Lasco; Miriam Barrett; Mayar Al Mohajer (Cambridge University Press, 2023)
Abstract Objective: To describe the use of next-generation sequencing (NGS) and to determine whether NGS leads to changes in antimicrobial management. Design and setting: This retrospective cohort study included patients aged ≥18 years admitted to a single tertiary-care center in Houston, Texas, with an NGS test performed between January 1, 2017, and December 31, 2018. Patients: In total, 167 NGS tests were performed. Most patients were of non-Hispanic ethnicity (n = 129), white (n = 106), and male (n = 116), with a mean age of 52 years (SD, 16). Moreover, 61 patients were immunocompromised: solid-organ transplant (n = 30), patients with human immunodeficiency virus (n = 14), and rheumatology patients on immunosuppressive therapy (n = 12). Results: Of the 167 NGS tests performed, 118 (71%) were positive. Test results associated with a change in antimicrobial management were found in 120 (72%) of 167 cases, with an average of 0.32 (SD, 1.57) fewer antimicrobials after the test. The largest change in antimicrobial management was in glycopeptide use (36 discontinuations) followed by antimycobacterial drug use (27 additions among 8 patients). Also, 49 patients had negative NGS results, but only 36 patients had their antibiotics discontinued. Conclusions: Plasma NGS testing is associated with a change in antimicrobial management in most cases. We observed a decrease in glycopeptide use after NGS results, which highlights physicians' comfort in withdrawing methicillin-resistant Staphylococcus aureus (MRSA) coverage. In addition, antimycobacterial coverage increased, corresponding with early mycobacterial detection by NGS. Further studies are needed to determine effective ways to use NGS testing as an antimicrobial stewardship tool.